2021
DOI: 10.1186/s12913-021-07023-w
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based practice in primary healthcare from the managerial point of view – a national survey

Abstract: Background The vast availability of and demand for evidence in modern primary healthcare force clinical decisions to be made based on condensed evidence in the form of policies and guidelines. Primary healthcare managers play a key role in implementing these governing documents. Thus, the aim of this article is to investigate the use and availability of evidence-based practice resources from the perspective of first-line primary healthcare managers. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…6 While the required information skillset must be acquired by each individual HP, the facilitation of EBP, in the form of ensuring the availability of support, resources, and a research culture, is the responsibility of the local management. [10][11][12][13][14][15] Managers are often recruited from the HP-staff within primary care with their own individual preunderstanding of EBP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 While the required information skillset must be acquired by each individual HP, the facilitation of EBP, in the form of ensuring the availability of support, resources, and a research culture, is the responsibility of the local management. [10][11][12][13][14][15] Managers are often recruited from the HP-staff within primary care with their own individual preunderstanding of EBP.…”
Section: Introductionmentioning
confidence: 99%
“…17 In their study of Swedish managers experiences of and attitudes toward working with EBP, Abelsson et al reported that knowledge of evidence and its impact in the local PHC is generally good. 12 However, the time devoted to gathering evidence and keeping up-to-date in their field varied. 12 Lack of time and knowledge about information resources has been identified as potential barriers to the implementation of EBP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The barriers to EBM practice can be related to personal, social, and work-related aspects. Overcoming the obstacles to EBM practice is critical for successfully implementing evidence-based practice in primary health care [ 33 , 34 ]. The findings of the present study suggest that age is one of the strongest predictors of evidence-based practice.…”
Section: Discussionmentioning
confidence: 99%
“…Where critical thinking and analysis of complex information are of paramount importance (2). These skills are essential in Evidence-Based Practice (EBP) as well (3)(4)(5). EBP is a process of merging the patient´s values and preferences with clinical expertise and the latest evidence to evaluate and give the best possible care to the patient (6,7).…”
Section: Introductionmentioning
confidence: 99%